Applicability of the early termination process in the intermediate stage and the effectiveness of the criminal process in the Tacna Judicial District, 2009-2013. - Chávez Torres, Wilber Alberto (2014)
Objective: Determine the feasibility of the application process early termination in the intermediate stage of the process, to ensure the effectiveness of the criminal proceedings in the judicial district of Tacna 2009 -2013. Method: The research is a form of Applied Research, because it is oriented in the application of knowledge to the solution of a problem, as the theory confronts reality. The Research Design is not experimental, transactional, descriptive and explanatory. Result: Were analyzed and interpreted the information processed through quantitative, qualitative analysis, and synthesis, determining the feasibility of the application process early termination in the intermediate stage of the process, to ensure the effectiveness of the criminal proceedings in the judicial district Tacna 2009 -2013. Conclusions: The normative regulation that limits the application of the early termination process in the intermediate stage, significantly affects the effectiveness of the criminal process. The application of the early termination process in the intermediate stage guarantees the principles that govern the common process. It also guarantees the exercise of the procedural rights of the parties; so it is feasible, in order to guarantee the effectiveness of the criminal process in the Judicial District of Tacna, 2009 -2013s